2019
DOI: 10.2460/javma.254.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a high-fidelity canine laparoscopic ovariectomy model for surgical simulation training and testing

Abstract: OBJECTIVE To develop and evaluate a high-fidelity simulated laparoscopic ovariectomy (SLO) model for surgical training and testing. DESIGN Evaluation study. SAMPLE 15 veterinary students (novice group), 5 veterinary surgical interns or residents (intermediate group), and 6 veterinary surgeons (experienced group). PROCEDURES Laparoscopic surgery experience was assessed by questionnaire and visual analog scales. Basic laparoscopic skills were assessed with a commercial training model. A commercial canine abdomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Validity is conceived as a hypothesis, where the collected validity evidence supports hypothesis' acceptance or rejection (56). This type of validation has been performed in human (57) and veterinary surgery (15,58,59). Unfortunately, a universally accepted model, including validation as a whole, with no fragmentation of validation levels, does not exist.…”
Section: Validation and Evaluation Of Surgical Skills In Laparoscopy Validation Of Surgical Skillsmentioning
confidence: 99%
“…Validity is conceived as a hypothesis, where the collected validity evidence supports hypothesis' acceptance or rejection (56). This type of validation has been performed in human (57) and veterinary surgery (15,58,59). Unfortunately, a universally accepted model, including validation as a whole, with no fragmentation of validation levels, does not exist.…”
Section: Validation and Evaluation Of Surgical Skills In Laparoscopy Validation Of Surgical Skillsmentioning
confidence: 99%
“…3,4,6,9,[22][23][24][25][26][27][28][29][30] Recent reports have described the development and validation of high-fidelity canine abdominal model laparoscopic simulators. 4,25,26 However, evidence regarding the transfer of skills from simulation to the veterinary operative setting remains limited. The authors have found no published reports on the level of proficiency in simulation-based training required to safely advance to a live-animal-based setting.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, general surgical skills do not broadly translate to laparoscopic surgical skills because of loss of depth perception on a two-dimensional video image, impaired hand-eye coordination, limitations on haptic feedback, angle of approach, instrument movement, and the fulcrum effect. [3][4][5][6][7] Overcoming these obstacles involves a steep learning curve even for experienced surgeons, and the risk of morbidity is increased when novice laparoscopic surgeons perform surgical procedures in live animals. 5,[8][9][10][11] Concerns for patient welfare, use of purpose-bred animals for teaching purposes, handling of cadavers, and costs associated with prolonged surgery in live patients have prompted a shift toward integration of simulation for instruction and assessment of laparoscopic skills in human and veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations